1988
DOI: 10.1002/1098-108x(198803)7:2<239::aid-eat2260070210>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Lay beliefs about disordered eating

Abstract: Although “disordered eating,” as a set of psychiatric conditions, implicitly evaluates components of a social phenomenon, little attention has been paid to the boundaries between socially accepted and abnormal eating. Lay knowledge and evaluations of the formal criteria for a diagnosis of anorexia nervosa or bulimia were therefore examined. The results show that although males and females know more about anorexia nervosa than bulimia, the DSM‐III criteria for anorexia nervosa, which involve the determined purs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 16 publications
1
9
0
2
Order By: Relevance
“…3 Over the past two decades, the beliefs of the public concerning the nature and treatment of the eating disorders anorexia nervosa (AN) and bulimia nervosa (BN) have been examined in a number of studies. [4][5][6][7][8][9][10][11][12][13][14][15][16] Several findings of interest have emerged from this research. First, the public is gen-erally optimistic about the prognosis of individuals with eating disorders who receive treatment, but pessimistic about outcome in the absence of treatment.…”
Section: Introductionmentioning
confidence: 83%
“…3 Over the past two decades, the beliefs of the public concerning the nature and treatment of the eating disorders anorexia nervosa (AN) and bulimia nervosa (BN) have been examined in a number of studies. [4][5][6][7][8][9][10][11][12][13][14][15][16] Several findings of interest have emerged from this research. First, the public is gen-erally optimistic about the prognosis of individuals with eating disorders who receive treatment, but pessimistic about outcome in the absence of treatment.…”
Section: Introductionmentioning
confidence: 83%
“…7 One study found that body dissatisfaction (preoccupation with weight/shape, wanting a flat stomach) was considered normal, whereas deviations in eating behavior (induced vomiting, spitting out food) were abnormal. 8 The perception that some ED symptoms are normal, together with evidence that social rejection is especially high for purging behaviors 9 suggests that stigmatizing attitudes toward AN and BN may differ. In support of this notion, Munstermann and Steins 10 found that participants sat closer to a confederate who they believed had AN than a confederate who they believed had BN.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, it would not be surprising to find that at least some women consider the symptoms of AN to be acceptable, or even desirable, given the extent to which thinness is idealised in contemporary Western societies and given that the low body weight and steadfast control over dietary intake that characterise AN are often linked to fame and wealth in the popular media (Gustafsson, Edlund, Kjellin, & Norring, 2008; Striegel‐Moore & Franko, 2003). It would be more surprising to find that the symptoms of BN are viewed as acceptable, given that BN is characterised by uncontrolled episodes of binge eating, purging behaviours, such as self‐induced vomiting and laxative misuse, and weight cycling (Hay, 2003; Huon, Brown, & Morris, 1998). Nevertheless, certain aspects of BN, such as the regular use of extreme weight‐control behaviours, might be viewed as acceptable or desirable in some sections of the community, particularly given the current concern surrounding the obesity ‘epidemic’ (Austin, 1999; Burns & Gavey, 2004).…”
mentioning
confidence: 99%